(3eGdG jSY GdWHjH LgOs - (3jhSa Hf ESeGYjd Hf EdjGS Hf CMeO, CHh GdeMGSf, fUjQ GdOjf GdNhjj GdTGaYqj GdHZOGOj GdeYQha HGHf GdcJHj,J (B754 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3aEfg deG cGf GdEfSGf , Hd GdMjhGf , LedI ef GdeQcHGJ GdYfUQjI hGdeJhdOGJ GdEeJRGLjI s
(3BNQgG (B:s
(3hdgG RgQ CUaQ , cCfgG GdNfOQjdi hgj eLQHI ai EdUGb GdLQGMGJ WQjI hjGHSI OQkG aGageg s
(3efbhdI ef fSNI GdeDdas
(3fSNI eNJdaI GdNWs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B288 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B144s
Keywords: (3GdWHs